Diagnosing scaling bottlenecks in 10 community conservation initiatives in southern and eastern Africa - Thomas Pienkowski; Matt Clark; Arundhati Jagadish; Aklei Albert; Mohanjeet Brar; Tarn Breedveld; Linda Chinangwa; Deepali Gohil; Deziderius Irumba; Ramzy Kanaan; Rose Peter Kicheleri; Phillip Kihumuro; et al. (Conservation Biology, 2026)
Scaling area‐based conservation, including initiatives led or comanaged by Indigenous Peoples and local communities, is a flagship goal of the Kunming‐Montreal Global Biodiversity Framework. Conservationists often aspire to scale initiatives, but this is rarely achieved in practice. Identifying and addressing factors that limit initiative adoption (i.e., bottlenecks) could improve scaling strategies. We used insightsfrom 84 expert surveys to identify potential risk factors and bottlenecks to scaling 10 community, area‐based initiatives in southern and eastern Africa. The number of reported potential risk factors and bottlenecks varied among initiatives. However, unfair benefit sharing, unequal decision‐making, inflexible rules, and top‐down leadership were frequently identified as bottlenecks. Although adopting initiatives had costs (e.g., increased local conflicts, reduced local access to natural resources and cropland), most experts believed these costs were offset by other benefits and thus did not constitute bottlenecks. Our results did not capture local perspectives, but they suggest scaling strategies that strengthen environmental governance may support more socially just and durable approaches to meeting area‐based conservation goals.

Leaf traits capture the effects of land use changes and climate on litter decomposability of grasslands across Europe - Claire Fortunel; Eric Garnier; Richard Joffre; Elena Kazakou; Helen Quested; Karl Grigulis; Sandra Lavorel; Pauline Ansquer; Helena Castro; Pablo Cruz; JiŘí DoleŽal; Ove Eriksson; et al. (Ecology, 2009)
Land use and climate changes induce shifts in plant functional diversity and community structure, thereby modifying ecosystem processes. This is particularly true for litter decomposition, an essential process in the biogeochemical cycles of carbon and nutrients. In this study, we asked whether changes in functional traits of living leaves in response to changes in land use and climate were related to rates of litter potential decomposition, hereafter denoted litter decomposability, across a range of 10 contrasting sites. To disentangle the different control factors on litter decomposition, we conducted a microcosm experiment to determine the decomposability under standard conditions of litters collected in herbaceous communities from Europe and Israel. We tested how environmental factors (disturbance and climate) affected functional traits of living leaves and how these traits then modified litter quality and subsequent litter decomposability. Litter decomposability appeared proximately linked to initial litter quality, with particularly clear negative correlations with lignin‐dependent indices (litter lignin concentration, lignin : nitrogen ratio, and fiber component). Litter quality was directly related to community‐weighted mean traits. Lignin‐dependent indices of litter quality were positively correlated with community‐weighted mean leaf dry matter content (LDMC), and negatively correlated with community‐weighted mean leaf nitrogen concentration (LNC). Consequently, litter decomposability was correlated negatively with community‐weighted mean LDMC, and positively with community‐weighted mean LNC. Environmental factors (disturbance and climate) influenced community‐weighted mean traits. Plant communities experiencing less frequent or less intense disturbance exhibited higher community‐weighted mean LDMC, and therefore higher litter lignin content and slower litter decomposability. LDMC therefore appears as a powerful marker of both changes in land use and of the pace of nutrient cycling across 10 contrasting sites.